Las transformaciones en el plano a través de los procesos de enseñanza y aprendizaje de la geometría en estudiantes de grado sexto - Tristancho Orduz, Mónica Julieth (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: The objective of this thesis work is to design and evaluate a didactic strategy to favor the teaching and learning processes of geometric transformations, making use of concrete material and dynamic systems of representation in the geometry class with sixth grade students. Most of the activities were developed in a face to face manner; however, one of the activities involving technological tools was developed during virtual classes, taking advantage of the mandatory confinement due to the COVID-19 pandemic. The analysis of the study was carried out having as theoretical reference the Pólya problem solving, mathematical visualization and the use of the Dynamic Geometry Software (DGS). Methodologically, the research adopted an interpretative phenomenological approach, with the purpose of exploring, describing and understanding the students' experiences regarding polygon transformations in the plane. Within the results, the difficulty that some students have in associating concepts and relating them to the daily context is highlighted; within these concepts, especially the reflection of polygons in the plane and rotation are found, especially when the manipulation of the grader is performed.